Improving English Speaking Skills Through the Utilization of Artificial Intelligence (AI) At SMK Swasta Emmanuel Agung in the Community Service Program - Yaredi Waruwu; Nurul Hikmah Giawa; Dwi Putri Juwita Zebua; Sovi Septia Diana Zebua; Meniati Zebua (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to improve vocational high school students’ English speaking skills through the utilization of Artificial Intelligence (AI)–based learning technology. The activity was conducted at SMK Swasta Emmanuel Agung and focused on addressing students’ low speaking confidence, limited opportunities for oral practice, and the lack of innovative learning media in English instruction. The implementation employed an experiential learning approach consisting of material presentation, demonstration, and direct speaking practice using an AI-based learning platform. Data were collected through observation, field notes, and activity documentation, and analyzed using descriptive qualitative techniques. The results indicate that the integration of AI technology in English learning positively influenced students’ speaking performance, particularly in terms of pronunciation accuracy, fluency, and self-confidence. Students demonstrated increased participation and motivation during speaking activities, supported by immediate feedback provided by the AI system. These findings suggest that AI-based learning serves as an effective and applicable instructional strategy for enhancing English speaking skills in vocational education. Therefore, the integration of Artificial Intelligence in English learning is recommended as a sustainable approach to support students’ communicative competence and readiness for the global workforce.